European ground squirrels Spermophilus citellus (Linnaeus) do not share identical Cryptosporidium spp. with North American ground squirrels - Jezkova, Jana; Holubova, Nikola; Kvicerova, Jana; Mateju, Jan; Sak, Bohumil; Kvac, Martin (Folia parasitologica, 2023)
Cryptosporidium Tyzzer, 1910 is one of the most common protistan parasites of vertebrates. The results of this study provide the first data on Cryptosporidium diversity in the European ground squirrel Spermophilus citellus (Linnaeus). A total of 128 faecal samples of European ground squirrels from 39 localities in the Czech Republic were analysed for the presence of Cryptosporidium spp. by microscopy and PCR/sequence analysis of small subunit ribosomal RNA (SSU) and the actin gene. While the microscopical examination did not reveal the presence of any Cryptosporidium oocysts, eight samples from six localities were PCR-positive. Phylogenetic analyses revealed the presence of five different Cryptosporidium spp. isolates. Four isolates, designated as Cryptosporidium sp. isolate Sc01-04, detected in wild populations and never recorded before, clustered closely to Cryptosporidium genotypes that have previously been found in North American ground squirrels' species. Cryptosporidium sciurinum Prediger, Ježková, Holubová, Sak, Konečný, Rost, McEvoy, Rajský et Kváč, 2021 was found in an animal sanctuary. Because C. sciurinum had previously been detected in Eurasian red squirrels Sciurus vulgaris Linnaeus at the same facility, it can be concluded that this Cryptosporidium was transmitted from tree squirrels to ground squirrels within the animal sanctuary. The results indicate that populations of European and North American ground squirrels are parasitised by different Cryptosporidium spp. At the same time, this is the first description of the occurrence of C. sciurinum in ground squirrels.
Keywords: fylogeneze; Cryptosporidiosis; kryptosporidióza; feces; zvířata; Animals; Severní Amerika; North America; Cryptosporidium; Feces; Phylogeny; Sciuridae